2021
DOI: 10.1093/bjs/znab237
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term survival after gastrectomy using random survival forests

Abstract: Background No well validated and contemporaneous tools for personalized prognostication of gastric adenocarcinoma exist. This study aimed to derive and validate a prognostic model for overall survival after surgery for gastric adenocarcinoma using a large national dataset. Methods National audit data from England and Wales were used to identify patients who underwent a potentially curative gastrectomy for adenocarcinoma of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…developed a 3D attention autoencoder-based survival prediction network for esophageal cancer using pretreatment CT images ( 28 ). Rahman and his colleges demonstrated that the Random Survival Forest model performed better than TNM stage for survival prediction of patients after esophagectomy ( 29 ). However, these studies generally have the disadvantages of small sample size and lack of external validation.…”
Section: Discussionmentioning
confidence: 99%
“…developed a 3D attention autoencoder-based survival prediction network for esophageal cancer using pretreatment CT images ( 28 ). Rahman and his colleges demonstrated that the Random Survival Forest model performed better than TNM stage for survival prediction of patients after esophagectomy ( 29 ). However, these studies generally have the disadvantages of small sample size and lack of external validation.…”
Section: Discussionmentioning
confidence: 99%
“…We can observe that age was the common risk factor for OS, RFS, and DSS, which is consistent with the previous study. 36 Since elderly patients tend to have many comorbidities and poor physical status, a comprehensive evaluation should be conducted by clinicians to select the appropriate treatment for them.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted November 29, 2022. ; https://doi.org/10.1101/2022.11.24.22281691 doi: medRxiv preprint Running Title: Multi-omics integration in Esophageal Adenocarcinoma reveals new possible biomarkers containing orthogonal RNA/Protein expression 3 change to columnar mucosa, known as Barrett's esophagus, which can progress over time through dysplasia to EAC 4 . If treated by resection at a mucosal-confined, often asymptomatic, early stage the 5-year overall survival approaches 90% 5 . However, despite recent advances in the detection and surveillance of Barrett's esophagus, the majority of patients with EAC still present with symptomatic, advanced disease, and the prognosis remains grave with a five-year overall survival of less than 20% 6,7 .…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%